An assessment of the value of electron microscopy in tumour diagnosis. Issue 4 (April 1985) - Fisher, C; Ramsay, A D; Griffiths, M; McDougall, J
Abstract : The contribution of electron microscopy to the diagnosis of tumours in a general hospital has been investigated. During a three year period 235 cases were examined, of which 66 (28%) were diagnostic problems by light microscopy. In 42 (64%) of the problem cases a contribution towards diagnosis was made by ultrastructural examination, which was most useful for anaplastic polygonal cell tumours, of some value for spindle cell neoplasms, and least helpful in the further categorisation of metastatic carcinoma.